Self-Perception, Knowledge and Awareness of Halitosis among Students of Higher Learning Institutions of Chitwan (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Halitosis is production of offensive odour coming out from oral cavity which most people try to avoid. It also leads to anxiety and social embarrassment. The people having halitosis have compromised quality of life. Hence this study was planned to assess the self-perception, knowledge and awareness of halitosis among students of higher learning institutions of Chitwan.MATERIALS AND METHODS: This was a descriptive cross-sectional study conducted among 280 students of higher secondary schools and colleges of Chitwan. The data collection was done from August 2021 to October 2021. A self-administered questionnaire was used. The results obtained were entered into Microsoft Excel 2019 and then transferred into Statistical Package for Social Science (SPSS) version 16. Descriptive statistical analysis was done. The study was analysed using frequency, percentages, mean and standard deviation.RESULTS: In this study, the mean age of the participants was 23.75 years. More than 90% of the participants belonged to 20-29 age group. Among the participants 44.3% reported of bad breath, while only 15.4% visited doctor and received treatment. Around 41.1% believed oral check-up as common diagnostic measures for halitosis and 40.4% had an opinion of consulting dentist for bad breath. The bad breath affected their social life behaviour, ended up friendship, stayed separate and away from friends and family. Around 64.5% were isolated from society.CONCLUSIONS: From our study we can conclude that halitosis is common problem in developing and developed nation. In the present study self-reported halitosis was present. The proper oral hygiene methods were lagging. Proper need of oral hygiene education and awareness campaign is therefore necessary.